Teaching Law Concept to University Students During Pandemic Situation: An Observational Study - Yusuf Faisal Ali (STAI Hubbulwathan Duri, 2022)
Teaching the concept of law to university students during the pandemic requires various efforts to foster an active participation of students. There are several strategies that can be carried out by optimizing communication technology in the division during the Covid 19 pandemic. To observe how a university implemented the teaching and learning concept of law, this study is conducted. This study was descriptive research with a qualitative approach as methods. The study was conducted through interview and observation. The data from interviews and observation was analyzed using three main steps, namely data reduction, verification, and data display. The study has resulted some findings: 1) communication technology as a means for education in the concept of rule of law in the academic community during the pandemic purposed to teach students about rights and obligations as good citizens, and 2) the campus had a role to provide the concept of a law state through student campus activity programs. Besides, the way out to deal with educational obstacles was also presented and discussed. In conclusion, the concept of a rule of law during a pandemic was to improve the quality of programs during learning within the Covid 19 pandemic.